Hedonic Test of Processed Products from Various Bok Choy (Brassica Rapa L.) Cultivation Techniques: Uji Hedonik Hasil Olahan Berbagai Produk Teknik Budidaya Pakcoy (Brassica rapa L.) - Calista Yulianti Putri Aditya; Jajuk Herawati; Indarwati (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2026)
Research this study aims to evaluate the level of consumer preference through a hedonic test of processed bok choy (Brassica rapa L.) juice from hydroponic, conventional, and microgreen cultivation. The parameters tested included taste, color, texture, aroma, and physical appearance. The results of statistical analysis (ANOVA) showed that cultivation techniques significantly affected all parameters except color. The microgreen technique was consistently the most preferred treatment by panelists with the highest average scores for taste (3.45), texture (2.84), aroma (3.36), and physical appearance (3.48). This superiority is thought to be related to the more intense concentration of volatile compounds in young plant tissue, while conventional techniques tended to obtain the lowest scores. The study concluded that in terms of organoleptic quality, bok choy with microgreen cultivation techniques had the best level of panelist acceptance.